Condições climáticas e comportamento ecofisiológico de espécies florestais - Galvão, Elayne Katia dos Santos (2018)
Climatic conditions are preponderant factors in the physiological behavior and growth of forest species, especially variations in temperature and atmospheric demand. In this sense, the present study investigated the influence of the conjugated effects of the vapor pressure deficit (VPD) and temperature variation on the eucalyptus and Paubrasilia echinata species aspects, seeking to understand the mechanisms of physiological acclimatization and growth. The study was conducted by mounting and driving two experiments presented in two chapters, the first one investigated three species of eucalyptus (Corymbia citriodora, Eucalyptus, camaldulensis and E. cloeziana) and the second two variants of P. echinata. Both experiments were conducted in greenhouse climatized with temperature and relative humidity of the air control, in a completely randomized design. Briefly were applied four treatments categorized as: Setting 1 (low atmospheric + low temperature demand, DPV ? + T ?), Environment 2 (VPD ? + T ?) Setting 3 (VPD ? + T ?) and Setting 4 (VPD ? + T ?). The first experiment lasted 62 days and the second 125 days. At the end of each experiment, growth parameters (height, diameter, leaf area and dry mass) and plant gas exchange were evaluated. The plants of C. citriodora, E. camaldulensis and E. cloeziana showed high efficiency in the use of water and stomatal control when submitted to the environment of high atmospheric demand associated with high temperature, so in this environment the species presented higher production of plant biomass and growth. The plants of the small and medium variants of P. echinata were divergent in growth in the environmental conditions evaluated. The small variant presented better acclimatization and higher growth in the environment of high atmospheric demand with high temperature, whereas the medium variant showed better acclimatization and higher growth in the lower temperature environments. It was noticed that the climatic variation in atmospheric demand and temperature triggered different mechanisms of physiological acclimatization occurring, sometimes, differentiations in growth between species (Eucalyptus) and within the same species (P. echinata).